European values as the basis of national cohesion, Ukraine's course towards European integration and strengthening the foundations of national security through education - Cherednychenko, O.; Trubavina, I. (New Collegium, 2023)
The article is devoted to the problem of the introduction of European values in the conditions of war and European integration.The authors prove that such work in the education system should be considered more widely today than in the field of traditional educational work. In particular, it is a consideration of the problem through the prism of national interests in the context of ensuring national security and social cohesion.The purpose of the article was to determine the essence and place of European values in national security through education, their relationship with national interests, the development of European integration processes and national cohesion, the role of an educator in this process.The scientific novelty of the study is that: for the first time, it was found that European values are a component of the national interests of Ukraine and a subject of national security in the activities of educators.They require teachers to master new functions: safety, informational, social assistance, as well as restoring the professional standard and filling the educational function with new content.These new functions of educators can act as a basis for improving the state of national security, the cohesion of the country and the community.European values as a guarantee of national security should become a component of the content of national education, in particular, moral, intellectual and spiritual, legal, etc.